The Court of Queen's Bench of Manitoba, 1870-1950 : a biographical history - Brawn, Dale, 1948- (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2006)
This fascinating study offers an intimate look at personalities ranging from prime ministers to members of the bench and both senior levels of government.
Keywords: Manitoba. -- Court of Queen's Bench -- Biography.; Manitoba. -- Court of Queen's Bench -- History.; Manitoba. -- Cour du banc de la reine -- Biographies.; Manitoba. -- Cour du banc de la reine -- Histoire.; Manitoba. -- Court of Queen's Bench; Judges -- Manitoba -- Biography.; Courts -- Manitoba -- History.; Juges -- Manitoba -- Biographies.; Tribunaux -- Manitoba -- Histoire.; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges.; LAW -- Civil Procedure.; LAW -- Legal Services.; POLITICAL SCIENCE -- Government -- Judicial Branch.; Courts; Judges; Manitoba; Biographies; History; Biographies.